Consistency Matters! How and When Does Corporate Social Responsibility Affect Employees’ Organizational Identification? - De Roeck, Kenneth; El Akremi, Assâad; Swaen, Valérie (Journal of Management Studies, 2016)
AbstractDespite the increasing attention to corporate social responsibility (CSR) in the management literature, little is known about the mechanisms and boundary conditions explaining employees’ responses to CSR. Drawing on social identity and cue consistency theory, we develop a mediated moderation model that explains how and under which conditions perceived CSR affects employees’ organizational identification. We test the model by carrying out a three‐wave longitudinal study on employees of an international utility company. The findings indicate that perceived CSR interacts with overall justice to predict organizational identification through the successive mediation of perceived external prestige and organizational pride. The study clarifies and advances some of the theoretical foundations surrounding the micro‐level approach of CSR and has key implications for management research and practice.